Association between childhood obesity, oral health behavior, and dental caries in Jetis, Yogyakarta - Narta Sari, Nikita; Hanindriyo, Lisdrianto; Priyono, Bambang (Faculty of Dentistry, Universitas Gadjah Mada, 2023)
The number of school-age children with overweight and obesity is increasing in developing countries. This is a risk factor for prosperity improvement followed by lifestyle changes. People with obesity are reported to be more susceptible to caries than people who are not, and the average numbers of caries in permanent molars increase on higher BMI. Dental caries is an infectious disease as a result of demineralization in enamel and dentine which has a relationship with behavior. The purpose of this study was to determine the relationship between oral health behavior and dental caries among overweight and obese children in Jetis District, Yogyakarta. This research was an analytical observational study with a cross sectional design. One hundred and ninety-six overweight and obese elementary school children in Jetis District were chosen using multistage cluster random sampling. The independent variable was behavior and the dependent variable was dental caries. Behavior variables were measured using questionnaire based on a Likert scale with validity testing (correlation coefficient > 0.30) and reliability testing (Cronbach alpha = 0.819). The caries was measured using teledentisry during the COVID-19 pandemic. Data analysis used Spearman’s correlation analysis. Behavior of maintaining oral and dental health in overweight and obese children had a relationship with caries (p < 0.001 and r = -0.410). There is no difference between overweight and obese children in maintaining their oral health behavior. The better the oral health behavior of the overweight and obese children, the lower the incidence of caries.